Mexico : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2010)
This Selected Issues paper analyzes the global crisis and potential growth in Mexico. The paper uses two methodologies to assess to what extent the global crisis is likely to weigh on Mexico's growth potential. The first approach is sectoral, examining the historical relationship between financial stress and growth in manufacturing industries. The second approach uses a growth-accounting framework to take a closer look at likely developments in the factors that drive potential growth. The paper also examines spending patterns and risks of expenditures volatility from unanticipated shocks in macroeconomic variables under two alternative fiscal rules.